Meningkatkan Ketahanan Duduk Menggunakan Teknik Behavior Contract Bagi Anak Gangguan Spektrum Autisme Kelas III di SLBN 1 Kamang Baru - Junior, Okta Prasetya; Efendi, Jon (Jurnal Penelitian Pendidikan Khusus, 2022)
In this study, the subject was a child with ASD at SLBN 1 Kamang Baru who had sitting endurance problems. Children are only able to sit for a duration 5 minutes, where the standard of sitting endurance for 3rd graders is 30-35 minutes. After conducting intense observations, the researchers found that children are sensitive to rewards and punishments. Researchers use this as a way to increase children’s sitting resistance. After searching for information, the researcher found a behavior contract technique. Behavior contracts are agreements made by teachers and children to change maladaptive behavior into adaptive behavior. In this study, the researcher used a SSR method with an A-B-A approach. Data recording is done by calculating the duration of sitting endurance through direct observation with the help of video recording. Data were analyzed using visual and graphic analysis. The results of the study stated that the duration of sitting endurance in children with ASD using contract behavior techniques increased during learning.